GAMBARAN FUNGSI GINJAL PADA PENDERITA SINDROM KORONER AKUT - Kristin, Albertha M.; Panda, A. Lucia; Pangemanan, Janry (Universitas Sam Ratulangi, 2016)
Abstract: Acute Coronary Syndrome (ACS) refers to a condition involving chest discomfort or other symptoms due to the lack of oxygen supply to the heart muscle due to coronary artery disorders. According to the 2008 World Health Organization (WHO) report, ACS is the first cause of death in the world with 12.8% mortality. Many studies confirmed that ACS was correlated with various factors that aggravated the kidney function. The formation of atherosclerotic lesions will cause constriction of the blood vessels resulting in decreased blood flow to the kidneys which leads to a decrease in Glomerular Filtration Rate (GFR). This study aimed to obtain the description of kidney function in patients with ACS. This was a descriptive study with a cross sectional design using secondary data from medical records of patients as a reference. Samples were 73 ACS patients. Most of the patients were in the age group 51-60 years. There were more male patients than females. GFR decline in patients with Unstable Angina Pectoris (UAP) was 27.17%; the Non ST-segment Elevation Myocardial Infraction (NSTEMI) was 40.74%; and ST-segment Elevation Myocardial Infraction (STEMI) was 72.73%. The co-morbidities were: Chronic Kidney Disease (CKD) 39.44%, hypertension 25.35% , diabetes 22.54%, and 12.68% as others. Conclusion: Most of the ACS patients were male, and the largest age group was 51-60 years. The most number of comorbidities was CKD and the largest decrease in GFR was in patients with STEMI. Keywords: renal function, glomerular filtration rate, ACS, CKD Abstrak: Sindrom Koroner Akut (SKA) merupakan suatu kondisi yang melibatkan rasa tidak nyaman pada dada atau gejala lainnya oleh karena kurangnya pasokan oksigen ke otot jantung akibat gangguan pada arteri koroner. Menurut laporan WHO tahun 2008, SKA merupakan penyebab kematian pertama di dunia dengan mortalitas 12,8%. Telah banyak penelitian yang mengatakan bahwa SKA berkorelasi dengan berbagai faktor yang memperberat kerja ginjal. Terbentuknya lesi aterosklerosis akan menyebabkan terjadinya konstriksi pembuluh darah sehingga terjadi penurunan aliran darah ke ginjal yang menyebabkan terjadinya penurunan Laju Filtrasi Glomerulus (LFG). Penelitian ini bertujuan untuk mendapatkan gambaran fungsi ginjal pada penderita SKA. Metode penelitian ialah deskriptif dengan desain potong lintang menggunakan data sekunder dari rekam medik pasien sebagai acuan. Jumlah sampel penelitian ini sebanyak 73 pasien. Penderita terbanyak pada kelompok usia 51-60 tahun, jenis kelamin laki-laki lebih banyak daripada perempuan. Penurunan LFG pada penderita Unstable Angina Pectoris (UAP) sebanyak 27,17%, Non ST-segment Elevation Myocardial Infraction (NSTEMI) 40,74% dan ST-segment Elevation Myocardial Infraction (STEMI) 72,73%. Penyakit penyerta pada kejadian SKA diantaranya Chronic Kidney Disease (CKD) sebanyak 39,44%, hipertensi 25,35%, diabetes 22,54% dan lain-lain 12,68%. Simpulan: Kelompok usia yang menderita SKA terbanyak adalah 51-60 tahun. Penderita SKA terbanyak berjenis kelamin laki-laki dan kelompok usia terbanyak ialah 51-60 tahun. Penyakit penyerta terbanyak ialah CKD dan penurunan LFG terbanyak pada penderita dengan STEMI.Kata kunci: fungsi ginjal, laju filtrasi glomerulus, sindrom koroner akut